PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMUNIKASI DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADAPT. BPR CINCIN PERMATA ANDALAS KABUPATEN PADANG PARIAMAN - Maria Magdalena; Andree Putra; Patria Nagara (Universitas Sumatera Barat, 2021)
Success in a company or organization cannot be separated from the role of company leaders incommunicating, motivating employees to get better productivity at work to achieve the company'sdesires. The problems that often occur at PT. BPR Cincin Permata Andalas is still the existence ofemployee negligence in carrying out the duties assigned by the leader, so that the duties given by theleader are not conveyed properly so that it can harm the company or agency, there are employeeswho do not understand the directions given by the leader so that employees cannot achieve the targetsset by the leader of the company. The purpose of this study was to determine the Effect ofTransformational Leadership, Communication and Work Motivation on Employee Productivity at PT.BPR Cincin Permata Andalas, Padang Pariaman Regency. This type of research is quantitative. Thenumber of respondents that can be used in this study are 49 employees of PT. BPR Cincin PermataAndalas. The results showed that transformational leadership had an effect on work productivity, theT value was 2.124 with a p value of 0.039. Communication has no effect on employee workproductivity, the T value is -1.186 with a p value of 0.242. Work motivation has an effect on workproductivity, the T value is 3.385 with a p value of 0.001. It is expected that companies will hold moreor condition employees to be more interactive among themselves, such as adjusting room positionsand work unit positions on a regular basis so that fellow employees can have more. a closerrelationship between their peers, or also increase the number of family gathering events so as to buildmore intense communication between fellow employees and also to the leadership